The effect of forensic medicine internship on the approach of fifth-year medical students to ethically controversial situations and forensic medical cases - Kılıç, Osman8; Hilal, Ahmet; Kaya, Kenan; Özesen, Toygün Anıl (The Bulletin of Legal Medicine, 2025)
Objective: This study aims to evaluate the changes in medical students’ approaches to forensic medical cases and situations involving medical ethical dilemmas before and after their forensic medicine internship, assess the retention of their knowledge when they become intern doctors, and identify deficiencies in forensic medicine education based on the study’s findings. Additionally, recommendations are proposed to address these deficiencies. Methods: The study evaluated 5th-year students at Çukurova University Faculty of Medicine during the 2022-2023 academic year. Surveys were conducted at three different times: before the internship, after the internship, and during the internship period. The pre-internship survey included statements probing their level of forensic medical knowledge and approaches to ethically controversial situations. The post-internship and internship period surveys included additional statements evaluating the education received during the forensic medicine internship. Data were analyzed using IBM SPSS Statistics 26. Results: The study included 307 participants who voluntarily completed face-to-face surveys before and after the forensic medicine internship, and 224 participants who voluntarily completed the survey via Google Forms during their internship period. Of those who found the forensic medicine education received in the 5th year sufficient for handling future situations encountered in their medical career, 91.9% (n=282) responded positively post-internship, compared to 70.1% (n=157) during the internship period. Those who knew the difference between a medical leave report and a forensic report were 24.4% (n=75) pre-internship, 88.9% (n=273) post-internship, and 75% (n=168) during the internship period. Regarding the statement, “Blood should be forcibly drawn by healthcare personnel from a...